2007
DOI: 10.1080/15622970600960165
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine in the treatment of psychotic adolescents: A case series of 23 patients with severe early onset psychosis

Abstract: Clinical efficacy, safety and tolerability of quetiapine in the treatment of 23 hospitalized psychotic adolescents were evaluated retrospectively. Twelve patients were changed to quetiapine from another antipsychotic medication during their hospital stay. In these patients, CGI-S improved from 4.75+/-0.87 to 2.92+/-0.67 (observation period 3.7+/-1.6 months). The most common adverse events were transient tachycardia and sedation. Mild EPS occurred only in one patient under quetiapine monotherapy. Transaminase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
2
9
1
Order By: Relevance
“…A previous study of rapid dose titration with high doses of quetiapine for treating acute psychotic cases revealed that the most common adverse event was sedation. In another such study, however, only one patient experienced transient somnolence [17,18]. In the present study, the incidence of somnolence did not differ significantly between the two initiation schedules, but one patient in the rapid initiation group dropped out because of intolerable somnolence.…”
Section: Discussioncontrasting
confidence: 59%
“…A previous study of rapid dose titration with high doses of quetiapine for treating acute psychotic cases revealed that the most common adverse event was sedation. In another such study, however, only one patient experienced transient somnolence [17,18]. In the present study, the incidence of somnolence did not differ significantly between the two initiation schedules, but one patient in the rapid initiation group dropped out because of intolerable somnolence.…”
Section: Discussioncontrasting
confidence: 59%
“…Quetiapine has usually been a relatively safe antipsychotic without any serious side eff ects even in adolescents [3,5,10,11] . Notwithstanding, some warnings about the possibility of hypothyroidism have been presented [2,12] . The overall safety of quetiapine in children under the age of 18 years has not been established yet [1] and the role of quetiapine in metabolic problems (weight gain, dyslipidemia, and blood glucose abnormalities), tardive dyskinesia, and sudden cardiac death have been discussed [13] .…”
Section: Discussion ▼mentioning
confidence: 99%
“…Quetiapine is usually well tolerated, severe side-eff ects are uncommon [5,10] . Sedation, postural hypotension, weight increase and increase in transaminases are the most important adverse eff ects [2] . A trend for a decrease in thyroxine (T 4 ) [2,11,12] , and in some cases also an increase in thyroid-stimulating hormone (TSH) have been reported [6,12] .…”
Section: Introduction ▼mentioning
confidence: 99%
See 1 more Smart Citation
“…In early reviews about the treatment of childhood-onset schizophrenia and psychotic disorders in general, the available studies already suggested the clinical eff ectiveness of quetiapine in these populations, but the authors [32,33] concluded that additional investigations are needed to confi rm these preliminary fi ndings. There are as yet no placebo-controlled studies, but in a recent double-blind 4-week comparison study, 200 mg / d quetiapine were compared with 400 mg / day quetiapine in drugna ï ve fi rst-episode psychosis patients, aged 15 -25 years and surprisingly, the 200 mg / day dose seemed to be more effi cacious with regard to early response rate [34] . 2 other recent open studies conclude that quetiapine at much larger doses may be an eff ective treatment in adolescents with a severe psychotic disorder (schizophrenia, acute schizophrenia-like disorder, schizoaffective disorder) [34,35] .…”
Section: Introduction ▼mentioning
confidence: 99%